Is bringing one's own alcohol to parties protective or risky? A prospective examination of sexual victimization among first-year college women. Issue 4 (19th May 2022) - Sell, Nichole M.; Testa, Maria
Abstract: Objective This study assessed whether college women who bring their own alcohol to parties (BYOB) are less vulnerable to sexual victimization (SV). Participants: Participants were 652 female freshmen ( M age = 18.04 years) at a large, public university. Methods: Women were recruited by email to complete online surveys of their drinking-related behaviors and sexual experiences in September (T1) and November (T2) of their first college semester. Results: Approximately 47% of our sample reported BYOB. Women who reported BYOB more frequently at T1 were more likely to report SV at T2 when accounting for risk factors, including prior SV, heavy episodic drinking, and hookups. Specifically, BYOB predicted contact and rape, but not coercion. Conclusions: Findings suggested BYOB does not prevent college SV, but rather may increase risk. We encourage college health professionals and researchers to target BYOB to better understand this common behavior and help students recognize potential for associated harm.